2020
DOI: 10.3389/fphar.2020.00823
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chinese Herbal Medicine Combined With Western Medicine on Vascular Endothelial Function in Patients With Hypertension: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Objective: Vascular endothelium plays a fundamental role in regulating endothelial dysfunction, resulting in structural changes that may lead to adverse outcomes of hypertension. The aim of this study was to systematically evaluate the effect of a combination of Chinese herbal medicine (CHM) and Western medicine on vascular endothelial function in patients with hypertension.Methods: We systematically searched the literature for studies published in Chinese and English in PubMed, Embase, Cochrane Central Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Three articles were excluded because one was a commentary, the other was a protocol, and the last used an animal model. The diversity of pathologies covered by the remaining articles is considerable, with three articles related to cancer (involving 54, 14 and 18 RCTs) [ 33 , 34 , 35 ], three related to hypertension (involving 30, 17 and 39 RCTs) [ 36 , 37 , 38 ], three related to COVID-19 (involving 19, 7 and 18 RCTs) [ 39 , 40 , 41 ], two related to depression (involving 40 and 16 RCTs) [ 42 , 43 ], two related to headache (involving 31 and 30 RCTs) [ 44 , 45 ], and the others related to allergic rhinitis (involving 17 RCTs) [ 46 ], spinal cord injury (involving 26 RCTs) [ 47 ], breast pain (involving 17 RCTs) [ 48 ], primary Raynaud’s phenomenon (involving 8 RCTs) [ 49 ], insomnia (involving 13 RCTs) [ 50 ], erectile dysfunction (involving 11 RCTs) [ 51 ], post-stroke spasticity (involving 35 RCTs) [ 52 ], irritable bowel syndrome with diarrhea (involving 21 RCTs) [ 53 ], diabetic kidney disease (involving 20 RCTs) [ 54 ], and Wilson’s disease (involving 18 RCTs) [ 55 ]. All articles reported the beneficial effects of Chinese herbal medicine when used as a primary treatment or adjunct therapy to Western medicine.…”
Section: Chinese Herbal Medicine and Dieteticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three articles were excluded because one was a commentary, the other was a protocol, and the last used an animal model. The diversity of pathologies covered by the remaining articles is considerable, with three articles related to cancer (involving 54, 14 and 18 RCTs) [ 33 , 34 , 35 ], three related to hypertension (involving 30, 17 and 39 RCTs) [ 36 , 37 , 38 ], three related to COVID-19 (involving 19, 7 and 18 RCTs) [ 39 , 40 , 41 ], two related to depression (involving 40 and 16 RCTs) [ 42 , 43 ], two related to headache (involving 31 and 30 RCTs) [ 44 , 45 ], and the others related to allergic rhinitis (involving 17 RCTs) [ 46 ], spinal cord injury (involving 26 RCTs) [ 47 ], breast pain (involving 17 RCTs) [ 48 ], primary Raynaud’s phenomenon (involving 8 RCTs) [ 49 ], insomnia (involving 13 RCTs) [ 50 ], erectile dysfunction (involving 11 RCTs) [ 51 ], post-stroke spasticity (involving 35 RCTs) [ 52 ], irritable bowel syndrome with diarrhea (involving 21 RCTs) [ 53 ], diabetic kidney disease (involving 20 RCTs) [ 54 ], and Wilson’s disease (involving 18 RCTs) [ 55 ]. All articles reported the beneficial effects of Chinese herbal medicine when used as a primary treatment or adjunct therapy to Western medicine.…”
Section: Chinese Herbal Medicine and Dieteticsmentioning
confidence: 99%
“…The diversity of pathologies covered by the remaining articles is considerable, with three articles related to cancer (involving 54, 14 and 18 RCTs)[33][34][35], three related to hypertension (involving 30, 17 and 39 RCTs)[36][37][38], three related to COVID-19 (involving 19, 7 and 18 RCTs)[39][40][41], two related to depression (involving 40 and 16 RCTs)[42,43], two related to headache (involving 31 and 30 RCTs)[44,45], and the others related to allergic rhinitis (involving 17 RCTs)[46], spinal cord injury (involving 26 RCTs)…”
mentioning
confidence: 99%
“…Some studies have declared that simultaneous use of more than one drug is a good strategy for treating DKD patients because of different mechanisms [75][76][77]. However, whether CHM should be used with ACEis or ARBs remained unexplored, even though use of CHM with ACEis or ARBs simultaneously may improve blood pressure control among hypertension patients [78]. Our study reported the rationale of combining an ACEi or ARB with CHM for DKD patients by presenting the long-term benefits and the different coverage of DKD-related proteins and molecular pathways.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Some studies have declared that simultaneous use of more than one drug is a good strategy for treating DKD patients because of different mechanisms [75][76][77]. However, whether CHM should be used with ACEis or ARBs remained unexplored, even though use of CHM with ACEis or ARBs simultaneously may improve blood pressure control among hypertension patients [78]. Our study reported the rationale of combining an ACEi or ARB with CHM for DKD patients by presenting the long-term benefits and the different coverage of DKD-related proteins and molecular pathways.…”
Section: Principal Findingsmentioning
confidence: 99%